2013
DOI: 10.1097/rlu.0b013e318286bbda
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Functioning Thyroid Nodules and 131I in Diagnosis and Therapy After 50 Years of Experience

Abstract: 131I therapy with a calculated dose is an effective treatment of AFTN. If a fixed dose is chosen, 16 mCi is often resolutive and for nodules <3 cm a dose of 10 mCi can suffice. Nodules >5 cm are eligible for surgery. TSH is the only parameter required to evaluate the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…AFTN was defined as a focal increased uptake on TS corresponding to a thyroid nodule larger than 10 mm detected by thyroid ultrasound (US) in six papers [21,[23][24][25][26][27], to a palpable nodule in one study [16] and to a palpable nodule confirmed by thyroid US in the remaining one [22]. Most of the studies enrolled patients in whom TS was performed using 99m Tc-pertechnetate as radiopharmaceutical while both 99m Tcpertechnetate and 123 I were employed by Iwata et al [21] and Reschini et al [22], whereas 131 I was used by Ronga et al [26]. The reference range for serum TSH was quite similar among the included studies ranging from 0Á3 to 0Á5 mU/L for lower limit and for higher limit, respectively.…”
Section: Qualitative and Quantitative Analysis (Meta-analysis)mentioning
confidence: 99%
See 2 more Smart Citations
“…AFTN was defined as a focal increased uptake on TS corresponding to a thyroid nodule larger than 10 mm detected by thyroid ultrasound (US) in six papers [21,[23][24][25][26][27], to a palpable nodule in one study [16] and to a palpable nodule confirmed by thyroid US in the remaining one [22]. Most of the studies enrolled patients in whom TS was performed using 99m Tc-pertechnetate as radiopharmaceutical while both 99m Tcpertechnetate and 123 I were employed by Iwata et al [21] and Reschini et al [22], whereas 131 I was used by Ronga et al [26]. The reference range for serum TSH was quite similar among the included studies ranging from 0Á3 to 0Á5 mU/L for lower limit and for higher limit, respectively.…”
Section: Qualitative and Quantitative Analysis (Meta-analysis)mentioning
confidence: 99%
“…The full text of six eligible articles was retrieved and two additional studies were found screening the references of the selected articles. Finally, eight articles including series of patients with AFTN were selected for the meta-analysis [16,[21][22][23][24][25][26][27] (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioiodine (RI) treatment has been increasingly used to solve hyperthyroid states, by applying different schemes of RI doses (low or high fixed dose as well as doses calculated on the basis of the nodule size or RI uptake after 123 I administration). The optimal dose of RI to silence the hyperfunctioning nodule, avoiding the development of hypothyroidism, is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In our study [2], 49% of the patients had a normal TSH value, but this proportion increased to 71% after exclusion of the patients addressed for the work-up of a low TSH. This information was not always present in the studies included in the meta-analysis of Treglia et al Nevertheless, the highest proportion of normal TSH value (80%) was observed in the study of G€ orges et al [4] that excluded patients with a known thyroid dysfunction, and one of the lowest proportions (29%) was observed in the study of Ronga et al [5] that included only patients referred for radioactive iodine treatment. Therefore, we believe that when AFTN is discovered in the work-up of a thyroid nodule, the proportion of patients with a normal TSH is even higher than reported in this metaanalysis.…”
mentioning
confidence: 99%